Geohazard features of the Central Apulia - Elisabetta Campiani; Fabio Trincardi; Federica Foglini; Giacomo Dalla Valle; Elisa Leidi; Alessandra Mercorella; Domenico Ridente (Journal of Maps)
The study area, mapped in the frame of the Magic project (MArine Geohazard along Italian Coasts) encompasses a complex continental slope characterised by a variety of extensive mass-transport deposits, seafloor-dissecting faults (Gondola deformation belt), and the deeply incised Bari Canyon System. Numerous fields of large-scale bedforms, and associated erosional features, record the impact of salt-rich contour-parallel and cold downslope-cascading shelf waters. Mass transport processes mobilise Pleistocene progradational deposits (made of sandy, partially lithified units), at the shelf edge, and/or open slope muds and/or contouritic sediment drifts; retrogressive failure may further affect the margin.